Interpreting the Bible in the "new" South Africa: Remarks on some problems and challenges - Human, Dirk J. (Hervormde teologiese studies, 1997)
Interpreting the Bible in the 'new' South Africa DJ Human Department of Biblical Studies (Sec B) University of Pretoria The Bible plays an important role in South African society. The interpretation of this book within or outside the Christian community has become an increaslingly major source of debate. It has been used and misused in several spheres of society. This article does not intend providing an extensive and composite picture of the problems and character of biblical hermeneutics. Nor will it attempt to elaborate on or explain the origins, development and influences of all the different her-meneutical approaches. Rather, it poses to be an introduction to a few of the problem(s) encountered in the attempt to understand the Bible, especially in terms of the 'new' South Africa. Within the framework of this scope, remarks will be made regarding the challenges involved in interpreting the Bible, the role of the interpreter in the interpretation process, the varied forms of literature to be found in Scripture, and in the last instance, to take cognisance of a few methodological approaches to the text analysis of the Bible.